Prevalence and characterization of treatment‐refractory psoriasis and super‐responders to biologic treatment: a nationwide study. (12th April 2022) - Loft, N.; Egeberg, A.; Rasmussen, M.K.; Bryld, L.E.; Nissen, C.V.; Dam, T.N.; Ajgeiy, K.K.; Iversen, L.; Skov, L.
Abstract: Introduction: Treatment with biologics often leads to clearance of psoriasis. However, some patients do repeatedly fail to respond and/or lose an achieved response (treatment refractory) to the biologic, whereas other patients achieve excellent response to one biologic and remain clear of psoriasis for several years (super‐responders). Objective: To identify and characterize patients with treatment refractory psoriasis and patients who are super‐responders to biologic treatment. Material and methods: Patients registered in DERMBIO between January 2007 and November 2019 were included. Patients were categorized as being treatment refractory if they had had treatment failure to ≥3 biologics targeting ≥2 different pathways. Super‐responders were patients treated with their first biologic for minimum 5 years without an absolute psoriasis area and severity index (PASI) > 3 between 6 months and 5 years of treatment. All remaining patients from DERMBIO served as comparators. Results: In total, 3280 patients were included with a mean age of 45.0 years. 1221 (37%) of the patients were females. Of the included patients, 214 (6.5%) were categorized as treatment refractory and 207 (6.3%) were categorized as super‐responders. Treatment refractory patients had higher mean body weight (100.6 kg vs. 90.6 kg, P < 0.0001) and higher mean BMI (32.2 vs. 29.4, P < 0.0001) compared with the rest of patients in DERMBIO. Super‐responders had higher socioeconomic status and fewer comorbidities compared with the comparator group ( P < 0.0001). Conclusion: A small proportion of patients with psoriasis treated with biologics are either super‐responders or treatment refractory. Treatment refractory patients have higher body weight, whereas super‐responders have fewer comorbidities and higher socioeconomic status.